Improving the Quality of MSME Marketing Via Social Media at the Hamed Kebab Business - Yunita, Ike Natalia Krisma (Universitas Nusantara PGRI Kediri, 2024)
Research aim: For know how can Hamed Kebab MSMEs in the village of Kampung England Pare increase marketing through social media. Design/Method/Approach: Study This is study purposive qualitative. For identify role social media in increase activity marketing owner of Hamed Kebab UMKM in English Village. Method data collection is carried out with technique interviews and observations. Research Finding: results from study This is can increase quality marketing via social media, you can help MSME owners in promotion manufacture content. Research limitation: The limitation of this research is that it exists lack of time is due owner difficult found.